ال فاعلية برنامج ارشاد مهني في تحسين الرضا الوظيفي وخفض ضغوطات العمل لدى المرشدين التربويين في المدارس الخاصة في محافظة اربد: لا يوجد - Qaoud, عبدالله (Jadara Journal of Social Sciences, 2025)
Abstract: The study aimed to identify the challenges that cause work-related stress for educational counselors in private schools in Irbid Governorate, and to examine the impact of a career counseling program on improving their job satisfaction. The study employed a qualitative descriptive-analytical approach on a sample of 15 counselors working in private schools in Irbid, who were selected purposefully. The results indicated that educational counselors face numerous challenges, such as insufficient resources, unclear job roles, and social and professional pressures, including the lack of a school culture that promotes job security.. The study also demonstrated a positive impact of the career counseling program in terms of time management improvement, personal effectiveness enhancement, and clarification of job roles, which reduced ambiguity regarding tasks. Moreover, the program helped in creating a balanced work environment that reduced job burnout and taught coping strategies for work-related stress, including techniques like meditation and deep breathing. The main recommendations was to provide ongoing career counseling programs that meet the needs of counselors, improve their working conditions, and ensure the availability of necessary resources.